Antithrombotic strategies in elderly patients with atrial fibrillation revascularized with drug-eluting stents: PACO-PCI (EPIC-15) registry. (1st September 2021) - de la Torre Hernandez, Jose M.; Ferreiro, José L.; Lopez-Palop, Ramon; Ojeda, Soledad; Marti, David; Avanzas, Pablo; Linares, Jose A.; Diego, Alejandro; Amat, Ignacio J.; Telleria, Miren; Cid, Belen; Otaegui, Imanol; et al.
Abstract: Background: We sought to investigate the antithrombotic regimens applied and their prognostic effects in patients over 75 years old with atrial fibrillation (AF) after revascularization with drug-eluting stents (DES). Methods: Retrospective registry in 20 centers including patients over 75 years with AF treated with DES. A primary endpoint of MACCE and a co-primary endpoint of major bleeding by ISTH criteria were considered at 12 months. Results: A total of 1249 patients (81.1 ± 4.2 years, 33.1% women, 66.6% ACS, 30.6% complex PCI) were included. Triple antithrombotic therapy (TAT) was prescribed in 81.7% and dual antithrombotic therapy (DAT) in 18.3%. TAT was based on direct oral anticoagulants (DOAC) in 48.4% and maintained for only 1 month in 52.2%, and DAT included DOAC in 70.6%. Primary endpoint of MACCE was met in 9.6% and primary endpoint of major bleeding in 9.4%. TAT was significantly associated with more bleeding (10.2% vs. 6.1%, p  = 0.04) but less MACCE (8.7% vs. 13.6%, p  = 0.02) than DAT and the use of DOAC was significantly associated to less bleeding (8% vs. 11.1%, p  = 0.03) and similar MACCE (9.8% vs. 9.4%, p  = 0.8). TAT over 1 month or with VKA was associated with more major bleeding but comparable MACCE rates. Conclusions: Despite advanced age TAT prevails, but duration over 1 month or the use of other agent than Apixaban are associated with increased bleeding without additional MACCE prevention. DAT reduces bleeding but with a trade-off in terms of ischemic events. DOAC use was significantly associated to less bleeding and similar MACCE rates. Highlights: Evidence regarding combination of antithrombotic agents in elderly patients with AF undergoing DES implantation is scarce. Randomized trials focused on elderly patients are hardly foreseeable, so large registries are required to enhance knowledge. This large multicenter registry provides valuable insights into the contemporary practice in this complex scenario. Triple strategy dominates, but beyond 1 month or without Apixaban bleeding was increased without additional MACCE prevention. Double therapy reduces risk of bleeding but with a trade-off in terms of ischemic cardiac events in a high-risk population.